Sucrose Derivatives Preparation using Thermomyces lanuginosus Lipase and Their Application - Ashrafuzzaman, Md; Pyo, Jung In; Cheong, Chan Seong (WILEY-V C H VERLAG GMBH, 2014)
We immobilized Thermomyces lanuginosus lipase to catalyze transesterification reaction in DMF. This lipase was selected after screening among other commercial lipases. We found that prepared immobilized lipase is particularly useful for preparation of 6-O-acylsucrose with higher conversion rate even in 10 g scale. Several solvents were evaluated for selective transesterification reaction. We noticed that the immobilized lipase retained more than 80 % activity after 5 cycles of 96 h reaction. A general method was also developed to purify the products using simple crystallization and precipitation process. Furthermore, 6-O-vinyladipoylsucrose was subjected to synthesis of the corresponding polymer by radical initiator. The sucrose branched polymer can be used further for evaluation of its biodegradability and other biological applications.
Keywords: ESTERS; SUGARS; CATALYSIS; ACYLATION; ENZYME